Pembuatan Media Pembelajaran Virus Influenza Berbasis Flash - William Sanjaya Suyanto; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2016)
The study of influenza virus is a very interesting needed topic to learn. In the learing process, high comprehension is because influenza  virus keeps on mutated. There is one way to undertand it easily is by using influenza virus learning media.This app will pack an information about infuenza virus by using interactive learning tools, where the players will actively play in the learning process,  starting from the information about flu burung, flu babi, and flu singapura. There is also a quiz to measure the ability of a user. From the questionnaire result and human computer interaction test, the application strongly supports the process of understanding the material. Therefore user’s interest in learning is increased, coupled with the easiness and user friendliness of application usage.